2017
DOI: 10.3892/ol.2017.7664
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of cisplatin cytotoxicity by Retigeric acid B involves blocking DNA repair and activating DR5 in prostate cancer cells

Abstract: Retigeric acid B (RAB), a natural compound isolated from lichen, has been demonstrated to inhibit cell growth and promote apoptosis in prostate cancer (PCa) cells. The present study evaluated the function of RAB combined with clinical chemotherapeutic drugs in PCa cell lines by MTT assay, reverse transcription quantitative polymerase chain reaction and western blot analysis, and identified that RAB at low doses produced significant synergistic cytotoxicity in combination with cisplatin (CDDP); however, no mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…In addition, multiple anti-cancer agents have been revealed to be used in combination with ddP to enhance treatment. For example, retigeric acid B, a topoisomerase ii inhibitor, can enhance the cytotoxicity of ddP in prostate cancer (47), while ursane triterpenoid can be combined with DDP in bladder cancer (48). Consistent with the studies that revealed that USP7 inhibitor can overcome bortezomib resistance in multiple myeloma cells (49), the present findings indicated the pharmacological potential of uSP51 inhibitors in the treatment of lung cancer.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, multiple anti-cancer agents have been revealed to be used in combination with ddP to enhance treatment. For example, retigeric acid B, a topoisomerase ii inhibitor, can enhance the cytotoxicity of ddP in prostate cancer (47), while ursane triterpenoid can be combined with DDP in bladder cancer (48). Consistent with the studies that revealed that USP7 inhibitor can overcome bortezomib resistance in multiple myeloma cells (49), the present findings indicated the pharmacological potential of uSP51 inhibitors in the treatment of lung cancer.…”
Section: Discussionsupporting
confidence: 86%
“…b-Thujaplicin, a natural monoterpenoid found in the wood of trees in the Cupressaceae family, sensitized osteosarcoma cells to damage caused by ionizing radiation, as it inhibits the formation of RAD51 foci and keeps RPA phosphorylated (113). Retiegeric acid B potentiates the effects of cisplatin on hormone-refractory prostate cancer cells by affecting nucleotide excision repair, particularly ERCC1, TFB5, and RPA1 proteins, and mismatch repair, presumably MSH2 and MSH6 proteins (114).…”
Section: Other Compoundsmentioning
confidence: 99%
“…Retigeric acid B, a natural pentacyclic triterpene acid isolated from the Lobaria, is a promising anticancer agent in prostate cancer cells. Liu et al (2018) have reported that when retigeric acid B was combined with cisplatin, which is also an anticancer treatment, including against prostate cancer, anticancer efficacy increased against PC-3 and DU-145, prostate cancer cells. Doxorubicin, etoposide, docetaxel, and vincristine were tested in combination.…”
Section: Resultsmentioning
confidence: 99%